Construction and EST sequencing of full-length, drought stress cDNA libraries for common beans (Phaseolus vulgaris L.) - Blair, Matthew W.; Fernández, A.C.; Ishitani, Manabu; Moreta Mejia, DE; Seki, M.; Ayling, S.; Shinozaki, Kazuo (Springer, 2011)
Background: Common bean is an important legume crop with only a moderate number of short expressed sequence tags (ESTs) made with traditional methods. The goal of this research was to use full-length cDNA technology to develop ESTs that would overlap with the beginning of open reading frames and therefore be useful for gene annotation of genomic sequences. The library was also constructed to represent genes expressed under drought, low soil phosphorus and high soil aluminum toxicity. We also undertook comparisons of the full-length cDNA library to two previous non-full clone EST sets for common bean.